Evaluation of efficacy and utility of spirometry data in elderly (>65years) individuals with or without lung diseases - Ponnathota, Vindhya; Gogineni, Sujatha; Kasireddy, Silpa (International Journal of Advances in Medicine, 2019)
Background: Spirometry is an important diagnostic monitoring tool for various lung disorders. Ventilatory function can be assessed by spirometry. Also, we can find whether it is obstructive or restrictive disease. An appropriate technique is essential to ensure accurate results. Spirometry requires proper understanding and cooperation of the patient while doing the test. The objective was to evaluate the efficacy and utility of spirometry data in elderly (>65years) individuals with or without lung diseases. Methods: A hospital based cross sectional study was carried out among 199 subjects who were then divided into 100 controls and 99 cases. Spirometry was carried out among all subjects. The values of spirometry were compared among cases and controls as well as across age and sex groups. Student’s t-test was applied. Results: After studying the spirometric data in elderly population with or without lung disease, there was significant difference between cases and controls as far as pack years of smoking was concerned. There was significant difference in FEV1, FVC and FEV1/FVC between the cases and controls. As the age increased the spirometric values decreased. The spirometry was normal in controls in majority compared to none in cases. Conclusions: Spirometry should be used by all primary care and specialist physicians even in elderly population.